Self-Ligating Brackets and Their Impact on Oral Health-Related Quality of Life in Chinese Adolescence Patients: A Longitudinal Prospective Study - Yu Zhou; MinLing Zheng; Jiaqiang Lin; Yi Wang; Zhen Yu Ni (The Scientific World Journal)
Introduction. Although the associations between orthodontic and oral health-related quality of life (OHRQOL) have been explored, little research has been done to address the influence of brackets type on perceived OHRQOL. The aim of this study was to assess whether the levels of OHRQOL in Chinese adolescence patients were influenced by the type of brackets. Materials and Methods. One hundred fifty Chinese orthodontic adolescence patients completed the 14-item Oral Health Impact Profile (OHIP-14, Chinese version) at five distinct intervals: after insertion of the fixed appliance at 1 week (T1), 1 month (T2), 3 months (T3), and 6 months (T4); and after treatment (T5). Results. Patients with self-ligating brackets were associated with less pain and discomfort at any intervals compared with conventional brackets, but no significant difference of overall OHIP-14 scores could be found between two groups. Moreover, in both groups, overall scores at T1 and T2 were significantly higher than the scores at any other intervals in both groups. Conclusions. The type of orthodontic appliance did not affect oral health-related quality of life in Chinese adolescence patients.